Terapia comportamental aplicada em contexto ambulatorial: um estudo exploratório das possíveis variáveis envolvidas na origem e manutenção de respostas que caracterizam anorexia e bulimia nervosa - Almeida, Paola Esposito de Moraes (2001)
This work was based on the Skinnerian model of selection by consequences and on the biobehavioral model of activity anorexia, in order to interpret the so called anorexia and bulimia nervosa, emphasizing the multiple determination of such eating disorder. The present study aimed at investigating the variables involved in the origin and maintenance of the eating disorders of four participants treated at an outpatient program for eating disorders of a university hospital (PROATA UNIFESP). The relationships between physical activity and eating restrictions (dieting), which are considered a risk for anorexia, as well as the acting contingencies probably involved on the maintenance of the eating disorders were investigated. The results indicated a probable relationship between exercising and feeding restrictions at the origin of the patients referred eating disorders, and allowed for the identification of the acting contingencies involved in their maintenance